"Decentring" international student mobility: The case of African student migrants in China. Issue 3 (13th October 2020) - Mulvey, Benjamin
Abstract: Despite the growth in numbers and geopolitical relevance of African students in China, research focusing on this body of student migrants remains scarce. This article presents an empirical investigation and postcolonial theorisation of student migration between Africa and China. Drawing on data from semi‐structured interviews with 40 African students, I provide an account of the decision‐making processes that lead African student migrants to study in Chinese universities. The article explores how this process is mediated by global power asymmetries, specifically China's position within the (post)colonial world system relative to African nations. Four examples are given of student decision‐making processes which are shaped by structural inequalities, and challenge existing understandings of who moves overseas to study for a degree and to what ends. These are as follows: underprivileged students benefiting from China's political manoeuvring, students who are coerced into moving overseas, students who are middle class but not affluent by global standards, and elites who take advantage of social networks to secure diplomatic scholarships.